Determination Of The Zero Point Of Building Construction In Area C Of Kadiri University With Polygon Mapping - Wiwit Mely Yanti Jannah; Zendy Bima Mahardana; Rama Putra Nugraha; Onie Wardani; Miya Setiyo Asih; Dwi Irin Mariana; Dodi Setiawan (Litbang Pemas - Universitas Islam Lamongan, 2022)
Area C of Kadiri University is an empty land located west of the campus area. The land is planned to construct buildings C, D, and E as a projected study area. In carrying out infrastructure development, it is necessary to have a mapping framework to coordinate building plans. Determining the zero point of action requires a land survey to determine the strategic position and the need for excavation or fill. The method used is a closed polygon with vertical and horizontal theodolite shooting tools. The results of the field details showed several projections of the building plan column from survey data on the location of the P1 device with coordinates 31900'43